2020
DOI: 10.1111/all.14228
|View full text |Cite
|
Sign up to set email alerts
|

Nasal specific IgE correlates to serum specific IgE: First steps towards nasal molecular allergy diagnostic

Abstract: relevance for the future improvement of clinical diagnostics, especially in children with allergic airway disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…AR and allergic asthma patients may profit from an earlier accurate local diagnosis before the disease is systemically detectable 36 . In this respect, Gökkaya and colleagues 37 have adopted the Immuno Solid‐phase Allergen Chip (ISAC) to measure aeroallergen‐specific IgE in nasal fluid, which might be the first step toward nasal molecular allergy diagnostic. The NAC has always been regarded as a useful tool for the diagnosis of AR and LAR and therefore might serve to design and monitor allergen immunotherapy 38 .…”
Section: Precise Diagnosis In Local Sitesmentioning
confidence: 99%
“…AR and allergic asthma patients may profit from an earlier accurate local diagnosis before the disease is systemically detectable 36 . In this respect, Gökkaya and colleagues 37 have adopted the Immuno Solid‐phase Allergen Chip (ISAC) to measure aeroallergen‐specific IgE in nasal fluid, which might be the first step toward nasal molecular allergy diagnostic. The NAC has always been regarded as a useful tool for the diagnosis of AR and LAR and therefore might serve to design and monitor allergen immunotherapy 38 .…”
Section: Precise Diagnosis In Local Sitesmentioning
confidence: 99%
“…A 2020 study by Gökkaya et The positive predictive value of nasal sIgE was 0.97 and that of serum sIgE was 0.96, whereas the negative predictive values were 0.82 and 0.92, respectively. As a possible cause of this lower sensitivity, the authors suggested the lack of manufacturers' instructions in terms of the optimal use of microarrays for nasal secretion specimens [23].…”
Section: Resultsmentioning
confidence: 99%
“…Die vorliegende Studie geht in vorbildlicher Art und Weise das Thema der evidenzbasierten Medizin an. Der Einbezug des Nasensekretes als Biomarkerquelle ist hoch innovativ [1] und könnte insbesondere bei Entzündungsprozessen der oberen Nasenwege die zukunftsweisende Biomarkerquelle sein [2]. Eine auch von den Autoren diskutierte Limitation besteht in der geringen Anzahl der Teilnehmenden.…”
Section: Transfer In Die Praxis Von Prof Dr Claudia Traidl-hoffmann A...unclassified